2008
DOI: 10.1530/rep-07-0478
|View full text |Cite|
|
Sign up to set email alerts
|

Development of single mouse blastomeres into blastocysts, outgrowths and the establishment of embryonic stem cells

Abstract: The recently developed technique of establishing embryonic stem (ES) cell lines from single blastomeres (BTMs) of early mouse and human embryos has created significant interest in this source of ES cells. However, sister BTMs of an early embryo might not have equal competence for the development of different lineages or the derivation of ES cells. Therefore, single BTMs from two-and four-cell embryos of outbred mice were individually placed in sequential cultures to enhance the formation of the inner cell mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 45 publications
(61 reference statements)
3
33
0
Order By: Relevance
“…Despite this, the blastocyst is the stage which has traditionally provided the highest derivation efficiencies [28] and, moreover, Wakayama and co-workers in the aforementioned study obtained the highest ESC derivation rates (88%) from blastocysts. This fact agrees with other authors' suggestion that the key aspect to derive ESCs is to have blastomeres with a defined ICM phenotype [29]. Moreover, it has been suggested that cell fate decisions could be earlier made at 2-and 4-cell stages [30][31][32].…”
Section: Discussionsupporting
confidence: 91%
“…Despite this, the blastocyst is the stage which has traditionally provided the highest derivation efficiencies [28] and, moreover, Wakayama and co-workers in the aforementioned study obtained the highest ESC derivation rates (88%) from blastocysts. This fact agrees with other authors' suggestion that the key aspect to derive ESCs is to have blastomeres with a defined ICM phenotype [29]. Moreover, it has been suggested that cell fate decisions could be earlier made at 2-and 4-cell stages [30][31][32].…”
Section: Discussionsupporting
confidence: 91%
“…Upon puncture, oocytes of primordial follicles were released from the somatic cells, collected manually under the microscope by mouth pipetting and washed with M2 medium prior to use. MII oocytes were collected as described (Lorthongpanich et al, 2008).…”
Section: Collection Of Primordial Follicles and MII Oocytesmentioning
confidence: 99%
“…These results demonstrate a pattern indicating that only 1 or 2, but not all blastomeres from each embryonic stage are capable of deriving ESCs, which might suggest that sister blastomeres are in general not equally competent for establishing ES cells lines (Lorthongpanich et al, 2008;Wakayama et al, 2007). Lorthongpanich et al could establish ESCs lines from isolated blastomeres of 2-cell stage embryos from CD-1 outbred mice strain but were unable to obtain lines from blastomeres coming from 4-cell stage embryos (Lorthongpanich et al, 2008). The pre-blastocyst period in the mouse development constitutes a stage in which blastomeres are not yet committed to either the ICM or the trophoectodermal lineage.…”
Section: Embryo Stages Capable Of Giving Rise To Mescsmentioning
confidence: 87%
“…The efficiency in establishing ESCs lines from blastomeres of 2-, 4-and 8-cell embryos decreased according to the stage, being higher when they came from 2-cell stage embryos. These results demonstrate a pattern indicating that only 1 or 2, but not all blastomeres from each embryonic stage are capable of deriving ESCs, which might suggest that sister blastomeres are in general not equally competent for establishing ES cells lines (Lorthongpanich et al, 2008;Wakayama et al, 2007). Lorthongpanich et al could establish ESCs lines from isolated blastomeres of 2-cell stage embryos from CD-1 outbred mice strain but were unable to obtain lines from blastomeres coming from 4-cell stage embryos (Lorthongpanich et al, 2008).…”
Section: Embryo Stages Capable Of Giving Rise To Mescsmentioning
confidence: 91%